Pesquisa em gastronomia no Brasil: configuração do campo e interfaces com a hospitalidade (1999-2016) - FERRO, Rafael Cunha (2018)
This exploratory-descriptive dissertation has documental nature and it characterizes as a State of the Art study of documents originating from strictu senso graduate programs of any area of knowledge in a national scope, that have direct relation with the Gastronomy. The main objective was to investigate the formation of the field of knowledge of Gastronomy in Brazil from the systematization of its academic production at the postgraduate level. The sample of this research counted on 223 theses (13%) and dissertations (87%) dated of 1999 and 2016 treated through the Analysis of Content. With the extraction of the type of document (dissertation or thesis), origin / institution / college, name of the program and year of defense, it was possible to classify the documents in 27 areas of knowledge, with a concentration in Tourism and Interdisciplinary areas, and 7 large areas of knowledge from CAPES, with greater concentration in Applied Social Sciences. The titles, abstracts, objectives and keywords were used to categorize the documents into 12 aspects (economical, technological, political and environmental; sociocultural, historical, hilosophical, educational, linguistic and communicational; psychological and nutritional) grouped into three approaches: commercial, non-commercial and health. On average, three out of five documents that composed the sample of this research deal with topics with non-commercial aspects of Gastronomy. With this systematization a model of thematic approaches of the field of Gastronomy was elaborated that was tested with the researches related to the field of Hospitality contained in the sample identifying and characterizing the interfaces between the two fields in a transversal way. It was observed the adherence of this model reinforcing the multi and interdisciplinary nature of research in the field of Gastronomy and its relations with the field of Hospitality. Hospitality was found in 25 researches in the field of Gastronomy covering its main theoretical dimensions, with focus on gift/reciprocity and commensality, even in researches of commercial approaches.